GenCoF: a graphical user interface to rapidly remove human genome contaminants from metagenomic datasets - Czajkowski, Matthew D; Vance, Daniel P; Frese, Steven A; Casaburi, Giorgio (Bioinformatics (Oxford, England), 2019)
The removal of human genomic reads from shotgun metagenomic sequencing is a critical step in protecting subject privacy. Freely available tools addressing this issue require advanced programing knowledge or are limited by analytical time and data load due to their server-based nature. Here, we compared the most cited tools for host-DNA removal using synthetic and real metagenomic datasets. Then, we integrated the most efficient pipeline in a graphical user interface to make these tools available without command line use. This interface, GenCoF, rapidly removes human genome contaminants from metagenomic datasets. Additionally, the tool offers quality-filtering, data reduction and interactive modification of any parameter in order to customize the analysis. GenCoF offers both quality and host-associated filtering in a non-commercial, freely available tool in a local, interactive and easy-to-use interface. GenCoF is freely available (under a GPL license) for Mac OS and Linux at https://github.com/MattCzajkowski/GenCoF. Supplementary data are available at Bioinformatics online.